Analisis Faktor Yang Berhubungan Dengan Tingkat Kecemasan Keluarga Pada Masa Pandemi Covid-19 Didaerah Desa Citeureup Kabupaten Bogor Provinsi Jawa Barat - Aisyiah Aisyiah; Intan Asri Nurani; Putri Sahara Riyanto (Malahayati Nursing Journal, 2022)
ABSTRACT Covid-19 is currently a pandemic in all countries in the world. This pandemic outbreak has a negative impact on the physical and psychological health of individuals and society. A family cluster is the spread of the coronavirus that comes from family members. The spread starts from someone who has already been infected and then spreads to other family members. In addition, families tend to experience other health problems. Such as excessive levels of anxiety about the spread of Covid-19. This study aims to determine the relationship between family knowledge, the experience of family members being infected with Covid-19, the stage of family development with the level of anxiety about Covid-19. The sample in this study amounted to 37 respondents. The sampling technique used was the non-probabilistic sampling technique. The research instrument consisted of a questionnaire about family knowledge, the experience of family members being infected with Covid-19, the stage of family development, and the level of anxiety about Covid-19. This questionnaire has been tested for validity and reliability with Cronbach's alpha coefficient of 0.615. Data were analyzed using descriptive statistics and inferential statistics, namely Chi-square to determine the relationship between family knowledge, the experience of family members being infected with Covid-19, and the stage of family development with anxiety levels about Covid-19. It is known that as many as 25 (67.6%) respondents do not have anxiety, 25 (67.6%) respondents have good family knowledge, 22 (59.5%) respondents have experience with family members infected with Covid-19 and 16 (43.2 %) respondents have a stage of family development with a family of adult children. With the Chi-square test, there is no relationship between family knowledge and family anxiety level (p-value 0.515), there is no relationship between the experience of family members being infected with Covid-19 and family anxiety level (p-value 0.066) and there is no relationship between developmental stage families with anxiety levels (p-value 0.639). Most of the respondents did not have anxiety about Covid-19, had good family knowledge, had the experience of being infected with Covid-19, and the stage of family development of adult children. Keywords: Covid-19, Family Knowledge, Anxiety Level    ABSTRAK Covid-19 saat ini menjadi pandemi di seluruh negara di dunia. Wabah pandemi ini memiliki dampak negatif pada kesehatan fisik dan psikologis individu dan masyarakat. Klaster keluarga adalah penyebaran virus corona yang berasal dari anggota keluarga. Penyebaran berawal dari seseorang yang sudah terlebih dahulu tertular lalu menularkannya pada anggota keluarga lain. Selain itu keluarga  cenderung mengalami permasalahan kesehatan lainnya. Seperti tingkat kecemasan yang berlebihan terhadap penyebaran Covid-19. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan keluarga, pengalaman anggota keluarga terinfeksi Covid-19, tahap perkembangan keluarga dengan tingkat kecemasan terhadap Covid-19. Sampel dalam penelitian ini berjumlah 37 responden. Teknik pengambilan sampel menggunukan teknik non-probabilistic sampling. Instrumen penelitian terdiri dari kuensioner angket tentang pengetahuan keluarga, pengalaman anggota keluarga terinfeksi Covid-19, tahap perkembangan keluarga dan tingkat kecemasan terhadap Covid-19. Kuesioner ini telah diuji validitas dan reabilitas dengan koefisien cronbach’s alpha 0,615. Data dianalisis menggunakan descriptive statistics dan inferential statistics yaitu Chi-square untuk mengetahui hubungan pengetahuan keluarga, pengalaman anggota keluarga terinfeksi Covid-19, tahap perkembang keluarga dengan tingkat kecemasan terhadap Covid-19. Diketahui sebanyak 25 (67,6%) responden tidak memiliki kecemasan, 25 (67,6%) responden pengetahuan keluarga baik, 22 (59,5%) responden memiliki pengalaman adanya anggota keluarga yang terinfeksi Covid-19 dan 16 (43,2%) responden memiliki tahap perkembangan keluarga dengan keluarga anak dewasa . Dengan uji Chi-square tidak ada hubungan antara pengetahuan keluarga dengan tingkat kecemasan keluarga (p-value 0,515), tidak ada hubungan antara pengalaman anggota keluarga terinfeksi Covid-19 dengan tingkat kecemasan keluarga (p-value 0,066) dan tidak ada hubungan antara tahap perkembangan keluarga dengan tingkat kecemasan (p-value 0,639). Responden sebagian besar tidak memiliki kecemasan terhadap Covid-19, pengetahuan keluarga yang baik, memiliki pengalaman terinfeksi Covid-19 dan tahap perkembangan keluarga anak dewasa. Kata Kunci : Covid-19, Pengetahuan Keluarga, Tingkat Kecemasan